Vocabulary Self Collection Strategy to Increase Vocabulary Mastery - Ria Kamilah Agustina; Maskhurin Fajarina (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This research focused on increasing vocabulary mastery by using of Vocabulary Self-Collection Strategy. This research used CAR as the design which conducted in two cycles. Each cycle consisted of plan, implementation, observation and reflection. This research has 20 students (15 female and 5 male) as the subject research. They are the ESP (English as Specific Purpose) students of Indonesian language and literature education in the second semester. The result showed that mean score of the first cycle was 67 while in the second cycle was 94.3. There is 27.3 improvement from cycle one to cycle two. In short, the application of Vocabulary Self-Collection Strategy can be applied as the strategy to improve vocabulary mastery to the students.